(untitled) - Lewis, John (new York, 2005)
This best-selling text by Lewis and Loftus provides an introduction to both the Java programming language and the techniques for writing high-quality programs. This book provides an object-oriented approach that naturally progresses in a way that beginning programmers easily understand by first using objects, then writing clases. The book is also known for providing an introduction to programming practices that leads to well-designed software solutions. The use of graphical user interfaces and event processing is covered in optional, self-contained Graphics Track sections at the end of each chapter. This book also comes with Addison-Wesley's CodeMate. This online program competency builder transforms a student's reading experience into a dynamic programming environment with a click of a mouse. CodeMate allows students to view, compile, run, and edit programming problems directly from the textbook without installing a compiler.
Keywords: Java (computer program language),Object-oriented programming (computer science)